History of the Akkadian Language (2 Vols) - Vita, Juan-Pablo (Handbook of Oriental Studies. Section 1 the near and Middle East Ser., 2021)
Intro -- ‎Contents -- ‎Preface -- ‎Figures and Tables -- ‎Abbreviations: Bibliographical -- ‎Other Abbreviations and Conventions -- ‎Notes on Contributors -- ‎Part 1. Introduction -- ‎Chapter 1. Research on the Akkadian Language (Streck) -- ‎Part 2. Teaching and Writing Akkadian in the Ancient Near East -- ‎Chapter 2. Teaching Akkadian in the Ancient Near East (Kleinerman) -- ‎Chapter 3. Akkadian and Cuneiform (Streck) -- ‎Chapter 4. Akkadian and Alphabetic Cuneiform (Roche-Hawley and Hawley) -- ‎Chapter 5. Akkadian and the Greek Alphabet (Graeco-Babyloniaca) (Lang) -- ‎Part 3. Akkadian Some General Trends of Its Development -- ‎Chapter 6. Classification of Akkadian within the Semitic Family (Hasselbach-Andee) -- ‎Chapter 7. Historical Morphology of Akkadian (Kouwenberg) -- ‎Chapter 8. A Historical Overview of Akkadian Morphosyntax (Arkhipov, Kalinin and Loesov) -- ‎Chapter 9. A History of the Akkadian Lexicon (Kogan and Krebernik) -- ‎Chapter 10. A History of Akkadian Onomastics (Pruzsinszky) -- ‎Part 4. Akkadian in the Fourth and Third Millennia BCE -- ‎Chapter 11. Old Akkadian (Sommerfeld) -- ‎Chapter 12. Eblaite (Kogan and Krebernik) -- ‎Part 5. Akkadian in the Second Millennium BCE Akkadian in Mesopotamia -- ‎Chapter 13. Old Babylonian (Streck) -- ‎Chapter 14. Middle Babylonian (van Soldt) -- ‎Chapter 15. Old Assyrian (Kouwenberg) -- ‎Chapter 16. Middle Assyrian (Jakob) -- ‎Part 6. Akkadian in the Second Millennium BCE Peripheral Akkadian -- ‎Chapter 17. Akkadian and the Amorites (Charpin) -- ‎Chapter 18. Akkadian in Syria and Canaan (Vita) -- ‎Chapter 19. Akkadian and the Hittites (Beckman) -- ‎Chapter 20. Akkadian in Egypt (Müller) -- ‎Chapter 21. Akkadian in Elam (Malbran-Labat) -- ‎Part 7. Akkadian in the First Millennium BCE -- ‎Chapter 22. Neo-Assyrian (Fales) -- ‎Chapter 23. (Early) Neo-Babylonian (Hess).